Cerebrospinal fluid levels of L‐glutamate signal central inflammatory neurodegeneration in multiple sclerosis. Issue 5 (9th October 2021) - Stampanoni Bassi, Mario; Nuzzo, Tommaso; Gilio, Luana; Miroballo, Mattia; Casamassa, Alessia; Buttari, Fabio; Bellantonio, Paolo; Fantozzi, Roberta; Galifi, Giovanni; Furlan, Roberto; Finardi, Annamaria; De Rosa, Arianna; et al.
Abstract: Excessive extracellular concentrations of L‐glutamate (L‐Glu) can be neurotoxic and contribute to neurodegenerative processes in multiple sclerosis (MS). The association between cerebrospinal fluid (CSF) L‐Glu levels, clinical features, and inflammatory biomarkers in patients with MS remains unclear. In 179 MS patients (relapsing remitting, RR, N = 157; secondary progressive/primary progressive, SP/PP, N = 22), CSF levels of L‐Glu at diagnosis were determined and compared with those obtained in a group of 40 patients with non‐inflammatory/non‐degenerative disorders. Disability at the time of diagnosis, and after 1 year follow‐up, was assessed using the Expanded Disability Status Scale (EDSS). CSF concentrations of lactate and of a large set of pro‐inflammatory and anti‐inflammatory molecules were explored. CSF levels of L‐Glu were slightly reduced in MS patients compared to controls. In RR‐MS patients, L‐Glu levels correlated with EDSS after 1 year follow‐up. Moreover, in MS patients, significant correlations were found between L‐Glu and both CSF levels of lactate and the inflammatory molecules interleukin (IL)‐2, IL‐6, and IL‐1 receptor antagonist. Altered expression of L‐Glu is associated with disability progression, oxidative stress, and inflammation. These findings identify CSF L‐Glu as a candidate neurochemical marker of inflammatory neurodegeneration in MS. Abstract : Cerebrospinal fluid levels of L‐glutamate signal central inflammatory responses in multiple sclerosis (MS). The association between cerebrospinal fluid (CSF) L‐Glu levels, clinical features, and inflammatory biomarkers in patients with MS remains unclear. In this study, we found that altered expression of L‐Glu is associated with disability progression, oxidative stress, and inflammation. These findings identify CSF L‐Glu as a candidate neurochemical marker of inflammatory neurodegeneration in MS.